Chemical Warehouse Operations: Experience from SWIFT Integrated Logistics Sdn. Bhd (Global Business Management Review (GBMR), 2020)
This article investigated the comprehensive risk management model practised at SWIFT Integrated Logistics chemical storage operations. The objective is to systematically illustrate the risk factors by identifying risks and mitigating them from the flow of the operation.  By reducing or containing the risk factors, we are able to provide a conducive, safe, secure working environment with initiatives toward zero-incident reporting cases. A qualitative research method was applied in this study. Respondents selected for this study were at the managerial level at SWIFT Integrated Logistics with experience working in warehouse operations for more than five years. SWIFT Integrated Logistics management wanted to diversify its warehouse customer's portfolio and accepted new business opportunities in chemicals warehouse storage. The move contributed greatly to the business strategy and finance, but they faced serious risk management issues, which resulted in six (6) incidents and raised the level of anxiety and concern among the warehouse team on health & safety issues. Future studies may look into additional strategies to implement a better warehouse risk management model or plan for a chemical warehouse. This study suggested that regular or continuous training should be provided to the staff. Basic first aid kit training is an example of the mandatory training that should be part of the job standard operating procedure. This paper contributes to the limited existing study on chemical warehouse operations. Experience and measures taken by SWIFT management may provide some ideas to improve the management of chemical warehouse for other warehouse operators. Although chemical warehouse operation safety is important, there is scarce academic research that explores this issue.